Chronic-binge ethanol feeding aggravates systemic dyslipidemia in Ldlr-/- mice, thereby accelerating hepatic fibrosis - Hoebinger, Constanze; Rajcic, Dragana; Silva, Beatriz; Hendrikx, Tim (Frontiers in Endocrinology, 2023)
Objective: Chronic ethanol consumption is known to cause alcohol-associated liver disease, which poses a global health concern as almost a quarter of heavy drinkers develop severe liver damage. Alcohol-induced liver disease ranges from a mild, reversible steatotic liver to alcoholic steatohepatitis and irreversible liver fibrosis and cirrhosis, ultimately requiring liver transplantation. While ethanol consumption is associated with dysregulated lipid metabolism and altered cholesterol homeostasis, the impact of dyslipidemia and pre-existing hypercholesterolemia on the development of alcohol-associated liver disease remains to be elucidated. Design: To address the influence of systemic dyslipidemia on ethanol-induced liver disease, chronic-binge ethanol feeding (NIAAA model) was applied to female C57BL/6J (wild type) mice and mice deficient for the low density lipoprotein receptor (Ldlr-/-), which display a human-like lipoprotein profile with elevated cholesterol and triglyceride levels in circulation. Respective control groups were pair-fed an isocaloric diet. Results: Chronic-binge ethanol feeding did not alter systemic lipid levels in wild type mice. While increased systemic cholesterol levels in Ldlr-/- mice were not affected by ethanol feeding, chronic-binge ethanol diet aggravated elevated plasma triglyceride levels in Ldlr-/- mice. Despite higher circulatory triglyceride levels in Ldlr-/- mice, hepatic lipid levels and the development of hepatic steatosis were not different from wild type mice after ethanol diet. Immunohistochemical assessment indicated a lower induction of infiltrating neutrophils in the livers of ethanol-fed Ldlr-/- mice compared to wild type mice. In line, hepatic mRNA levels of the pro-inflammatory genes Ly6g, Cd11b, Ccr2, and Cxcl1 were reduced, indicating less inflammation in the livers of Ldlr-/- mice. In contrast, Ldlr-deficient mice developed more liver fibrosis after ethanol diet than wild type mice, as indicated by increased levels of Sirius Red staining and higher expression of pro-fibrotic genes Tgfb and Col1a1. Ldlr-/- and wild type mice had similar plasma ethanol levels and did not show differences in the hepatic mRNA levels of Adh1 and Cyp2e1, important for ethanol metabolism. Conclusion: Our results highlight that systemic dyslipidemia in Ldlr-/- mice accelerates the development of hepatic fibrosis after chronic-binge ethanol feeding, independent of hepatic lipid levels.